HERMENEUTIKA KRITIS MOHAMMED ARKOUN DAN RELEVANSINYA TERHADAP HISTORISITAS SERTA OTENTISITAS - Rido jamallius; Saskia Handayani (Universitas Islam Negeri Imam Bonjol Padang, 2026)
Contemporary hadith studies continue to rely predominantly on sanad (chain of transmission) and matan (textual) criticism as the primary methods for assessing the historicity and authenticity of hadith narrations. Although these approaches possess a strong methodological foundation, they have not fully addressed the historical, social, political, and epistemological dimensions that shape the formation, transmission, and legitimization of hadith. This study aims to examine the relevance of Mohammed Arkoun's critical hermeneutics in analyzing the historicity and authenticity of hadith through the concepts of Applied Islamology, l'impensé, and epistemological deconstruction. The research employs a library research method with a qualitative-descriptive approach by analyzing Arkoun's major works alongside contemporary scholarly literature on hermeneutics and hadith studies. The findings indicate that Arkoun's critical hermeneutics offers an alternative interpretive framework for reexamining the formation of hadith from a more historical, contextual, and reflective perspective by uncovering epistemological dimensions that are not fully addressed by classical hadith criticism. The principal finding of this study is the formulation of an integrative model that combines classical sanad and matan criticism with Mohammed Arkoun's historical-hermeneutic approach, enabling the assessment of hadith historicity and authenticity to extend beyond the validity of transmission by incorporating historical context, social dynamics, and the construction of knowledge underlying hadith traditions. This integrative model contributes to the advancement of contemporary hadith methodology by synthesizing the normative framework of classical hadith scholarship with perspectives from the social sciences and humanities, thereby fostering a more comprehensive, critical, and contextually relevant understanding of hadith in the contemporary intellectual landscape.